PENEGAKAN HUKUM KEIMIGRASIAN TERHADAP WARGA NEGARA ASING DALAM PENYALAHGUNAAN VISA IZIN TINGGAL YANG MELEWATI BATAS WAKTU (OVERSTAY) DI WILAYAH KOTA SUKABUMI - Dimas Leo Vernandho; Ujuh Juhana (INTELIGENSIA MEDIA, 2024)
The development of globalization has led to increased movement of people, goods, and services between countries, making it easier to cross borders for various human activities such as trade, tourism, and industry. While this has positive effects, it also brings negative consequences, such as the emergence of issues related to the legal or illegal movement of people, often accompanied by offenses and crimes, which are commonly referred to as immigration violations. The high number of foreign nationals overstaying their residence permits highlights the need for effective law enforcement to reduce such violations. Law enforcement efforts can be pursued through monitoring and enforcement measures as outlined in the Immigration Act No. 6 of 2011. This study employs empirical juridical research with a qualitative approach, utilizing data collection methods such as literature reviews, interviews, and observations. The study concludes that immigration law enforcement against foreign nationals who overstay their visas is not sufficiently effective, due to factors such as limited human resources in immigration offices and a lack of reports from the local community. To address this, immigration authorities should conduct outreach to educate the public on how to report suspicious activities involving foreign nationals.